Effect of α-tocopherol supplementation in diluents on the motility, viability and plasma membrane integrity of Simmental bull spermatozoa after cooling - Azura, Sarah; Ratnani, Hermin; Susilowati, Suherni; Hariadi, Mas'ud; Samik, Abdul; Soepranianondo, Koesnoto (Ovozoa: Journal of Animal Reproduction, 2020)
Semen storage in cold temperatures might cause an increase in reactive oxygen species (ROS) production. This condition resulted in spermatozoa damage and quality decrease. This study was conducted to investigate the effects of α-tocopherol supplementation in diluents on the motility, viability, and plasma membrane integrity of Simmental bull spermatozoa after cooling. Semen samples were diluted in skim milk egg yolk supplemented with 0, 0.5, 1.0, and 1.5 mM α-tocopherol respectively for control, Tl, T2, and T3. Spermatozoa were evaluated for their motility, viability, and membrane integrity in cooling temperature (5°C). The daily evaluation showed that 1.5 mM α-tocopherol was the best in maintaining motility, viability, and plasma membrane integrity, while 1.0 mM α-tocopherol was only good for maintaining viability. Therefore, it can be concluded that α-tocopherol at the concentration of 1.5 mM was an efficient antioxidant supplement for Simmental cattle semen in skim milk egg yolk diluent.